If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(12) * 2 + log(12) * x = log(12)(x + 7) Reorder the terms for easier multiplication: 12 * 2glo + log(12) * x = log(12)(x + 7) Multiply 12 * 2 24glo + log(12) * x = log(12)(x + 7) Reorder the terms for easier multiplication: 24glo + 12glo * x = log(12)(x + 7) Multiply glo * x 24glo + 12glox = log(12)(x + 7) Reorder the terms: 24glo + 12glox = glo * 12(7 + x) Reorder the terms for easier multiplication: 24glo + 12glox = 12glo(7 + x) 24glo + 12glox = (7 * 12glo + x * 12glo) 24glo + 12glox = (84glo + 12glox) Add '-12glox' to each side of the equation. 24glo + 12glox + -12glox = 84glo + 12glox + -12glox Combine like terms: 12glox + -12glox = 0 24glo + 0 = 84glo + 12glox + -12glox 24glo = 84glo + 12glox + -12glox Combine like terms: 12glox + -12glox = 0 24glo = 84glo + 0 24glo = 84glo Solving 24glo = 84glo Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-84glo' to each side of the equation. 24glo + -84glo = 84glo + -84glo Combine like terms: 24glo + -84glo = -60glo -60glo = 84glo + -84glo Combine like terms: 84glo + -84glo = 0 -60glo = 0 Divide each side by '-60'. glo = 0.0 Simplifying glo = 0.0 The solution to this equation could not be determined.
| 2x^3+12=0 | | -7-13=15 | | -4x+2y=34 | | 2x+7=-3x+8 | | (4x+7)=(7x-8) | | (6a^4b^3)(3ab^2)= | | X-4+12=12-2 | | 6xy*xy*4y= | | 2(4y-2)= | | (x+3)+(x-3)=1 | | (x+3)+(x-3)=0 | | 6(y+9)-56= | | 3x+11y=-7 | | 4+3x=32 | | 2/x=1/4 | | n+9=36 | | -22=2y-8 | | -7y+21x=49 | | D-2.7=2+2D | | 8y-2=-16 | | -5/2=2x/5 | | 45=6w-w | | x^2-112=(-3) | | 2xL+W=P | | f^2-6f+8= | | 3x^2+11=181 | | Y-10/3=0 | | 10=x^2+11x+40 | | Y-10/3=3 | | 5(2x-1)+x=9x+5 | | 0.10(x+40)+0.30x=8 | | 5/4*1/7 |